Linkages Between Nutrient Resorption and Ecological Stoichiometry and Homeostasis Along a Chronosequence of Mongolian Pine Plantations - Wang, Kai; Wang, G. Geoff; Song, Lining; Zhang, Risheng; Yan, Tao; Li, Yihang (Frontiers in Plant Science, 2021)
Nutrient resorption is an important strategy for nutrient conservation, particularly under conditions of nutrient limitation. However, changes in nutrient resorption efficiency with stand development and the associated correlations with ecological stoichiometry and homeostasis are poorly understood. In the study, the authors measured carbon (C), nitrogen (N), and phosphorus (P) concentrations in soil and in green and senesced needles along a chronosequence of Mongolian pine (Pinus sylvestris var. mongolica) plantations (12-, 22-, 31-, 42-, 52-, and 59-year-old) in Horqin Sandy Land of China, calculated N and P resorption efficiency (NRE and PRE, respectively), and homeostasis coefficient. The authors found that soil organic C and total N concentrations increased, but soil total P and available P concentrations decreased with stand age. Green needle N concentrations and N:P ratios as well as senesced needle C:N ratios, NRE, and PRE exhibited patterns of initial increase and subsequent decline with stand age, whereas green needle C:N ratios and senesced needle N concentrations, and N:P ratios exhibited the opposite pattern. NRE was positively correlated with N concentration and N:P ratio, but negatively correlated with C:N ratio in green needles, whereas the opposite pattern was observed in senesced needles. PRE was negatively correlated with senesced needle P concentration, soil-available N concentration, and available N:P ratio. The homeostatic coefficient of N:P was greater when including all stand ages than when including only those younger than 42 years. These findings indicate that tree growth may change from tending to be N limited to tending to be P limited along the Mongolian pine plantation chronosequence. Nutrient resorption was coupled strongly to tree growth and development, whereas it played a lesser role in maintaining stoichiometric homeostasis across the plantation chronosequence. Therefore, adaptive fertilization management strategies should be applied for the sustainable development of Mongolian pine plantations.